1987
DOI: 10.1093/ajcn/45.2.462
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium, vitamin antioxidants, and cardiovascular mortality: a 9-year follow-up study in the Netherlands

Abstract: The association between low serum selenium, vitamin A, and vitamin E levels and mortality from cardiovascular disease (CVD) was investigated in a case-control study nested in a 9-yr prospective study in the Netherlands. For 10,532 persons aged greater than or equal to 5 yr who participated in a 1975-1978 medical survey, serum was stored at -20 degrees C. For the 84 of 106 subjects aged 37-87 yr who died of CVD after the baseline exam, 168 cohort members alive at the end of 1983 and matched for age and gender w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1
3

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(54 citation statements)
references
References 26 publications
1
49
1
3
Order By: Relevance
“…In several prospective (3)(4)(5) and case-control (6) studies, low serum selenium levels were associated with increased risk of coronary heart disease. However, in other studies, this association could not be confirmed (7)(8)(9)(10). Antioxidant defense is achieved by additive or synergistic action of enzymes and antiox-idant nutrients (11,12).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In several prospective (3)(4)(5) and case-control (6) studies, low serum selenium levels were associated with increased risk of coronary heart disease. However, in other studies, this association could not be confirmed (7)(8)(9)(10). Antioxidant defense is achieved by additive or synergistic action of enzymes and antiox-idant nutrients (11,12).…”
mentioning
confidence: 80%
“…The question of whether low selenium status predisposes to cardiovascular disease has been addressed in a number of studies in the past decade (3)(4)(5)(6)(7)(8)(9)(10). In several prospective (3)(4)(5) and case-control (6) studies, low serum selenium levels were associated with increased risk of coronary heart disease.…”
mentioning
confidence: 99%
“…Presumably, this was also the case in US Physicians whose retinol lacked any prediction of CHD [13]. A Dutch study in men and women of broad age-range, which included low retinol levels [21] probably lacked significance because of gender differences and the age-dependent rise in plasma retinol in males [1,22].…”
Section: Vitamin Amentioning
confidence: 99%
“…Serum selenium concentrations seem to decrease with age (2,3) and are lower in persons with cancer and chronic diseases (3). Low serum/plasma selenium concentrations have been associated with increased mortality from cancer (4,5) and increased all-cause mortality among community-dwelling older men and women in France (6) and women in the USA (7).…”
Section: Introductionmentioning
confidence: 99%